2013
DOI: 10.1002/dta.1450
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the urinary threshold concentration of formoterol in sports drug testing

Abstract: The use of formoterol in sports is allowed by inhalation at the maximum recommended therapeutic dose. Recently, a threshold concentration of 30 ng.mL(-1) was defined by the World Anti-Doping Agency (WADA) to distinguish between therapeutic and forbidden use of formoterol. The objective of this work was to evaluate that threshold concentration. Concentrations of formoterol were measured in urine samples collected after administration of 18 µg of inhaled formoterol to five healthy volunteers, and in samples coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…The maximum recorded individual urine level (Table ) of rac ‐formoterol (free plus glucuronide) was 13.4 ng/mL which is in broad agreement with previous work that has been undertaken at higher doses . Previous reports have demonstrated a maximum concentration of 19.6 ng/mL total drug (free plus glucuronide) following a dose of 18 μg over 8 hours (one‐third of daily limit) but most routine samples were below 10 ng/mL .…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…The maximum recorded individual urine level (Table ) of rac ‐formoterol (free plus glucuronide) was 13.4 ng/mL which is in broad agreement with previous work that has been undertaken at higher doses . Previous reports have demonstrated a maximum concentration of 19.6 ng/mL total drug (free plus glucuronide) following a dose of 18 μg over 8 hours (one‐third of daily limit) but most routine samples were below 10 ng/mL .…”
Section: Resultssupporting
confidence: 88%
“…This has led to criticisms that the current threshold concentration is too high and that further validation is required. 25 While our work did not correct for urine-specific gravity, other single-dose pharmacokinetic studies with high dose inhaled salbutamol has demonstrated that exercise and dehydration do affect urine concentrations compared to rest, resulting in a greater risk of exceeding the WADA decision limit, but correcting for specific gravity results in only modest improvements. 26 Although free formoterol enantiomers have been previously measured following inhalation (albeit at high dose 10 ), to our knowledge, this is the first report of total urine formoterol enantiomer levels (free plus glucuronide) following inhaled dosing, and only the second study to report total urine formoterol enantiomer levels in urine (the previous report followed oral dosing).…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…[109] The LC was equipped with a C-8 analytical column (2.1 x 50 mm, particle size 1.8 μm) and the triple quadrupole (QqQ) mass spectrometer was operated in positive ESI and MRM mode. [111] Urine samples were collected up to 24 h and analyzed using an earlier reported GC-MS-based detection method. Moreover, the stability of formoterol in urine under different pH conditions was tested and the target analyte was found to be stable under normal physiological and commonly applied sample storage conditions.…”
Section: Beta-2-agonistsmentioning
confidence: 99%